The effect of large values of relative surface roughness on heat transfer and pressure drop characteristics in the laminar, transitional, quasi-turbulent, and turbulent flow regimes - Everts, Marilize (University of Pretoria, 2023)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2023.